2019
DOI: 10.1007/s11056-019-09745-6
|View full text |Cite
|
Sign up to set email alerts
|

How climate change might affect tree regeneration following fire at northern latitudes: a review

Abstract: Climate change is projected to increase fire severity and frequency in the boreal forest, but it could also directly affect post-fire recruitment processes by impacting seed production, germination, and seedling growth and survival. We reviewed current knowledge regarding the effects of high temperatures and water deficits on post-fire recruitment processes of four major tree species (Picea mariana, Pinus banksiana, Populus tremuloides and Betula papyrifera) in order to anticipate the effects of climate change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 179 publications
0
36
0
Order By: Relevance
“…Several studies have confirmed the influence of precipitation regime and soil conditions on jack pine establishment in the boreal forest [77][78][79]. Jack pine generally performs better than black spruce in dry conditions [25,[80][81][82]. Well-drained surface deposits, including till, fluvio-glacial expanses and lacustrine and sandy deposits, promote jack pine growth [83][84][85][86].…”
Section: Jack Pinementioning
confidence: 98%
See 2 more Smart Citations
“…Several studies have confirmed the influence of precipitation regime and soil conditions on jack pine establishment in the boreal forest [77][78][79]. Jack pine generally performs better than black spruce in dry conditions [25,[80][81][82]. Well-drained surface deposits, including till, fluvio-glacial expanses and lacustrine and sandy deposits, promote jack pine growth [83][84][85][86].…”
Section: Jack Pinementioning
confidence: 98%
“…Future climate change will directly affect tree growing conditions in the boreal forest zone [92]. In eastern Canada, tree species will be particularly vulnerable to temperature increases [25]. Our analyses allowed us to identify regional, stand and microsite variables that affect the growth of recently planted black spruce and jack pine seedlings.…”
Section: Conclusion and Implications For Forest Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Extreme fires in the past decade have raised concerns that the ecological resilience of (Girard et al 2009(Girard et al , 2011Whitman et al 2018bWhitman et al , 2019. The probability of post-fire tree regeneration failure is expected to increase across forests types in the future with the projected increase in fire activity, warm temperatures, and drought (Whitman et al 2018b;Splawinski et al 2019;Boucher et al 2020).…”
Section: Fire and Forest Dynamicsmentioning
confidence: 99%
“…There is still a gap in the information on the outplanting performance after a severe fire in relation to seed-source provenance for both species, causing concerns of the appropriate seed sources for restoration under climatic change context. Severe fires are known to cause losses of organic matter and nutrients, increases soil erosion 31 and spatial variation of the soil properties, decreases in site productivity 32 , and plant growth, and survival 33 , and decreases in post-fire recruitment 34 . As seedlings experience higher rates of mortality in the first year after planting, monitoring the early performance can give guidelines for achieving restoration goals.…”
Section: Introductionmentioning
confidence: 99%